2015
DOI: 10.17221/103/2014-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Identification of S-genotypes of sweet cherry cultivars from Central and Eastern Europe

Abstract: Lisek A., Rozpara E., Głowacka A., Kucharska D., Zawadzka M. (2015): Identification of S-genotypes of sweet cherry cultivars from Central and Eastern Europe. Hort. Sci. (Prague), 42: 13-21.Sweet cherry is a species that is characterized by self-incompatibility, which causes difficulties in obtaining high yields of sweet cherry fruit. Determination of the composition of the S-alleles of sweet cherry cultivars is useful both to growers producing the fruit and breeders when selecting cultivars for cross-fertiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
3
10
3
Order By: Relevance
“…The identification of the cultivars in the collection was carried out according to the UPOV (International Union for the Protection of New Varieties of Plants) descriptors of the fruit shape, color, taste, firmness of the flesh, shape of the stone, characteristics of the stalk, and other morphological features of the tree, leaves, and flowers. To confirm the cultivars identification, genetic identity analysis was performed, using PCR-based methods [12,13]. Main characteristics of the selected cultivars are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of the cultivars in the collection was carried out according to the UPOV (International Union for the Protection of New Varieties of Plants) descriptors of the fruit shape, color, taste, firmness of the flesh, shape of the stone, characteristics of the stalk, and other morphological features of the tree, leaves, and flowers. To confirm the cultivars identification, genetic identity analysis was performed, using PCR-based methods [12,13]. Main characteristics of the selected cultivars are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies showed that some S-alleles are more frequent in some regions and that certain alleles are specific to a particular geographic region. Among the identified S-alleles, a relatively higher frequency of occurrence (> 20%) of alleles S1 and S3, as well as for S1, S3 and S4 were reported respectively by TOBUTT et al (2004) and LISEK et al (2015), while the S9 allele occurred with similar frequency (about 6%). CACHI and WÜNSCH (2014) showed that alleles S3 and S6 are highly frequent all over Europe, while in northern and central Europe the most frequent are S1, S3, S4 and S6, compared to southern Europe where S3, S6 and S22 alleles are the most common.…”
Section: S-genotypes Of Parental and Derived Sweet Cherry Cultivarsmentioning
confidence: 88%
“…Although a capillary genetic analyzer is able to discriminate fragments differing by 1 nucleotide (nt), doubts may arise concerning fragment identity, and it is therefore recommended to run a control sample with known S-alleles in parallel. Furthermore, the S13 allele is nearly unamplifiable by these primers [ 12 , 23 ]. The primers PaConsII-F and PaConsII-R [ 19 ] were therefore developed to detect length polymorphisms of the second S-RNase intron, but PCR products must be analyzed by agarose gel electrophoresis due to their sizes (up to nearly 2.5 kbp), which reduces the resolution of the analysis.…”
Section: Introductionmentioning
confidence: 99%